The integration of literature in English Language proficiency courses / Chittra Muthusamy, Elangkeeran Sabapathy & Rasaya Marimuthu - Muthusamy, Chittra; Sabapathy, Elangkeeran; Marimuthu, Rasaya (2008)
The purpose of the study was to explore the possibility of integrating literature in English Language proficiency courses as it is far more rewarding and effective in enhancing language proficiency specifically in essay writing. It is the contention of the researchers that students lacking in content knowledge will perform poorly in their language ability and their essays will mirror such deficiency, limitations and shortcomings. An integrated literature based language curriculum can overcome these weaknesses. To prove this point a quasi experimental study was conducted on two BEL 200 intact groups from the Hotel and Catering programme; the control and experimental groups. Both groups underwent a four week experiment whereby one short story The Burden of Sin by S. Karthigesu was taught to the control group using the routine reading and comprehension teaching approach while the experimental group was taught using the reader response approach adapting Ibsen 's The I Model text exploration and literary devises. A pretest was administered in the first week and a posttest administered in the fourth week. Descriptive and inferential statistics were collected and analyzed. Two non parametric tests were run. The results proved to be substantially significant to the study. Conclusively by integrating literature into proficiency courses, we can observe that this can promote simultaneous learning of academic content, English Language skills, critical thinking abilities and maturity in weighing cross-cultural issues; all important factors which are of national interest in ensuring a successful nation.